2017
DOI: 10.3346/jkms.2017.32.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Soluble Receptor for Advanced Glycation End Products (sRAGE) and S100A12 (EN-RAGE) with Mortality in Long-term Hemodialysis Patients

Abstract: Hemodialysis (HD) patients experience vascular calcification, ultimately leading to high mortality rates. Previously, we reported associations between soluble receptor for advanced glycation end products (sRAGEs) and extracellular newly identified RAGE-binding protein S100A12 (EN-RAGE) and vascular calcification. Here, we extended our observations, investigating whether these biomarkers may be useful for predicting cardiovascular morbidity and mortality in these subjects. Thus, we evaluated the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…The role of sRAGE as a predictor of mortality in patients on dialysis is still under debate. The few studies that have been performed in this field up until now failed to observe any association [ 22 , 24 26 ]. Only a single study observed a trend, although not statistically significant, towards increased mortality with higher rather than lower sRAGE levels [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of sRAGE as a predictor of mortality in patients on dialysis is still under debate. The few studies that have been performed in this field up until now failed to observe any association [ 22 , 24 26 ]. Only a single study observed a trend, although not statistically significant, towards increased mortality with higher rather than lower sRAGE levels [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a link between levels of sRAGE with parameters of inflammation, oxidative stress, atherosclerosis, and heart failure (HF) in CKD-G5D [ 16 20 ], prior studies failed to observe a strong association with patient outcomes [ 21 24 ]. However, there are a limited number of studies in this field, and they are difficult to compare due to differences in study design and patient features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some mechanisms have been proposed, among which inflammation and its related brain injury play the key roles (Cerejeira, Nogueira, Luís, Vaz-Serra, & Mukaetova-Ladinska, 2012;Neerland et al, 2016;Vasunilashorn et al, 2017). It plays a crucial role in immune response and acts as a damage-associated molecular pattern protein, signaling through the receptor for advanced glycation end products (RAGE) (Jung et al, 2017;Khorramdelazad et al, 2015;Zhao et al, 2016). Treatment comprises both nonpharmacologic and pharmacologic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…S100A12 is a member of the S100 gene family of calcium-binding proteins. It plays a crucial role in immune response and acts as a damage-associated molecular pattern protein, signaling through the receptor for advanced glycation end products (RAGE) (Jung et al, 2017;Khorramdelazad et al, 2015;Zhao et al, 2016). Clearly, RAGE has been found in the central nervous system and emerges as a central regulator of brain inflammatory processes (Hu et al, 2018;Li et al, 2017;Villarreal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%